CMR-driven immunosuppressive therapy in systemic sclerosis patients with suspected myocarditis: a single-center experience. (3rd October 2022) - Bombace, S; Maurina, M; De Santis, M; Motta, F; Selmi, C; Rodolfi, S; Viggiani, G; Gasparini, G; Stefanini, G; Condorelli, G; Francone, M; Monti, L
Abstract: Background: Systemic sclerosis (SSc) myocarditis is common, but often underrecognized due to absence of symptoms at early stages. Cardiac Magnetic Resonance (CMR) is the imaging modality of choice for detection of SSc myocarditis. Current guidelines recommend CMR in case of alterations in first level cardiologic diagnostic tests. Immunosuppressive therapy is only indicated for patients with organ involvement, i.e. most frequently heart and lung, or with diffuse cutaneous systemic sclerosis. Purpose: To explore the impact of CMR in the diagnostic and therapeutic pathway of SSc patients. Methods: Of 286 SSc patients referred to our hospital, we retrospectively enrolled patients who received CMR during an observational period of 6 years (2016–2022). Exclusion criteria were previous immunosuppressive therapy and cardiopathy from other cause. Clinical data including Holter-ECG performed within 90 days from CMR were available. Results: 39 patients (67 [58–72] years; females 87%) were identified. 15 patients were excluded due to previous immunosuppressive therapy (9), lack of information on therapy (3), cardiopathy from other causes (3). 24 patients were finally included in the study. 14 patients (58%) did not show myocardial inflammation at CMR (LVEF 65.5 [61–69]%, LVEDV 114.5 [92–141] ml, T2 ratio 1.6 [1.4–1.9]). 1 patient presented with mid-wall inferior late gadolinium enhancement (LGE) indicative of previous myocarditis. 1 patient received immunosuppressive therapy due to SSc lung involvement in follow-up. In this group premature ventricular contractions (PVCs) during 24-hours Holter-ECG were rare (29 [3–48]). When measured, high-sensitivity Troponin I (hsTnI) was 2.4 [0.8–5] ng/L. 10 patients (42%) showed myocardial inflammation at CMR: LVEF 60 [56–65] %, LVEDV 137, 5 [122–166] ml, T2 ratio 2.1 [1.7–2.3], T1 mapping 1022.5 [1010–1036] msec and T2 mapping 50.5 [50–52] msec. Myocardial LGE with non-ischemic pattern was seen in 6 patients. The number of PVCs at 24-hours Holter-ECG was collectively higher in these patients (354 [1–4245]). When measured, hsTnI was 8 [6–18] ng/L. With detection of myocardial inflammation at CMR all 10 patients eventually received immunosuppressive therapy (mycophenolate mofetil (MMF) or azathioprine in case of MMF intolerance). At follow-up CMR performed 4 [3–6] months later on therapy various parameter differences were observed: LVEF (+2 [−2; 4] %), T1 mapping (−23 [−27; −12] msec), T2 mapping (−2 [−4; −1] msec), T2 ratio (−0.5 [−0.6; −0, 2]). Of 6 patients with LGE, 4 displayed LGE persistence at follow-up. Conclusions: In our experience, CMR was the tool of choice for diagnosis and therapeutic management in SSc patients with suspected cardiac involvement. SSc myocarditis patients tended to display more arrhythmic burden at Holter-ECG and higher cardiac biomarkers. Our data suggest to intensify first level cardiological screening, in order to identify suitable candidates to CMR. Funding Acknowledgement: Type of funding sources: None.